Você está na página 1de 2

2π

π

π

2

0

rdrdθ

4

4cosθ

0

7

rdrdθ

D xydA D

R (x + y)dA R y

x 2 + y 2 = 1 x 2 + y 2 =

R cos(x 2 + y 2 )dA R x

x 2 + y 2 = 9

D e x 2 y 2 dA D x = 4 y 2

y

R arctg( x )dA R = {(x, y)|1 x 2 + y 2 4, 0 y x}

4

y

r = cos(3θ)

r = cosθ r = senθ

r = 1 + cosθ r = 3cosθ

z = x 2 + y 2 x 2 + y 2 4

x 2 y 2 + z 2 = 1 z = 2

a

x 2 + y 2 + z 2 = 1

x 2 + y 2 = 4 4x 2 + 4y 2 + z 2 = 64

z = x 2 + y 2

3 3 0

9x 2

sen(x 2 + y 2 )dydx

1

0

2y 2

y

(x + y)dxdy

2

0

0

2xx 2

x 2 + y 2 dydx

1

2

1

1x 2 xydydx + 2

x

1

x

0

xydydx +

2 2 4x 2

0

xydydx

33π/2

π/12 16 π

3

1

2

πsen(9)

π (1 e 4 )

2

3

64 (π) 2

4 π

3

8 (π 2)

1

4 πa 3

3

( 2π )(1 ( 2 ))

3

1

1/2π(1 cos9)

2 2/3

( 8π )(64 24 3)

3